2014
DOI: 10.1186/bcr3598
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated p-70S6K predicts tamoxifen resistance in postmenopausal breast cancer patients randomized between adjuvant tamoxifen versus no systemic treatment

Abstract: IntroductionActivation of the phosphatidylinositol-3-kinase (PI3K) and/or mitogen-activated protein kinase (MAPK) pathways results in anti-estrogen resistance in vitro, but a biomarker with clinical validity to predict intrinsic resistance has not been identified. In metastatic breast cancer patients with previous exposure to endocrine therapy, the addition of a mammalian target of rapamycine (mTOR) inhibitor has been shown to be beneficial. Whether or not patients on adjuvant endocrine treatment might benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
67
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 35 publications
(49 reference statements)
9
67
0
Order By: Relevance
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…Alterations in the PI3K/AKT pathway, mainly PIK3CA mutations, have been shown most frequent in the luminal subtypes, suggesting a crosstalk between ER and PI3K/AKT [3]. Aberrant PI3K/AKT signalling has been connected to poor response to anti-oestrogen therapies in several studies [20,[42][43][44][45][46][47][48][49][50]. In the present study, we showed PTPN2 gene loss as a new potential marker of endocrine resistance.…”
Section: Discussionsupporting
confidence: 62%
“…The S6K1 antibody demonstrated high specificity and could serve as a clinical biomarker. Overactivated S6K has been suggested an upcoming prognostic and treatment predictive marker in ER-positive breast cancer (Noh et al 2008, Kim et al 2011, Beelen et al 2014. Here, we did not detect worse prognosis with high activity of the S6Ks, instead a somewhat improved prognosis was observed in the tamoxifen-untreated subset of patients when pS6K was highly expressed in the nucleus.…”
Section: Discussionsupporting
confidence: 52%
“…Here, we did not detect worse prognosis with high activity of the S6Ks, instead a somewhat improved prognosis was observed in the tamoxifen-untreated subset of patients when pS6K was highly expressed in the nucleus. Recently, Beelen et al (2014) have shown an improved prognosis with high levels of pS6K expression in the cytoplasm. It has been suggested that the p31 short isoform of S6K1 is the primary oncogenic protein in the S6K family (Rosner & Hengstschlager 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the mTOR pathway, which is a known predictor of endocrine resistance (14), was found to be elevated in the liver metastases of patients 1 and 3 at the transcript level in comparison with the primary tumor ( Supplementary Fig. S2).…”
Section: Metastatic Gene Expression Alterations Are Heterogeneous In mentioning
confidence: 99%